2014
DOI: 10.1007/s00726-014-1856-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human serine racemase activity and dynamics by halides, ATP and malonate

Abstract: D-Serine is a non-proteinogenic amino acid that acts as a co-agonist of the NMDA receptors in the central nervous system. D-Serine is produced by human serine racemase (hSR), a homodimeric pyridoxal 5'-phosphate (PLP)-dependent enzyme that also catalyzes the physiologically relevant β-elimination of both L- and D-serine to pyruvate and ammonia. After improving the protein purification yield and stability, which had so far limited the biochemical characterization of hSR, we found that the catalytic activity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…However, plant SRs represent a distinct group in eukaryotic serine racemases 9 and are thus likely to be all insensitive to nucleotide binding. Interestingly, the communication between active site and the ATP binding site is bidirectional, with the affinity for ATP increasing in the presence of active site ligands such as glycine and malonate 18 , 23 . The occupation of the active site by substrates and/or inhibitors leads to conformational changes in the small domain, which rotates with respect to the large domain to restrain accessibility to the active site 14 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, plant SRs represent a distinct group in eukaryotic serine racemases 9 and are thus likely to be all insensitive to nucleotide binding. Interestingly, the communication between active site and the ATP binding site is bidirectional, with the affinity for ATP increasing in the presence of active site ligands such as glycine and malonate 18 , 23 . The occupation of the active site by substrates and/or inhibitors leads to conformational changes in the small domain, which rotates with respect to the large domain to restrain accessibility to the active site 14 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…As shown above, the comparison of the structure of SpSR in the absence and presence of the ATP analog AMP-PCP (PDB 1V71 and 1WTC) revealed a change in the relative orientation of the major and minor domain (Goto et al, 2009), resulting in a wider back groove. Moreover, in the presence of ATP and either glycine or malonate, hSR active site appears less accessible than in the absence of ATP, as demonstrated by PLP fluorescence quenching (Marchetti et al, 2015). Moreover, by monitoring PLP fluorescence in the absence and presence of ATP, it was demonstrated that ATP binding to hSR promotes a decrease in the polarity of the active site, diminishing its accessibility (Marchetti et al, 2013).…”
Section: Sr Small Ligands and Protein Interactorsmentioning
confidence: 99%
“…The structure of fission yeast SR in complex with the ATP analogue AMP-PCP shows that 14 residues are involved in ATP binding (Goto et al, 2009). The racemase activity of human SR is increased by ATP (Marchetti et al, 2013(Marchetti et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%